NAFKAH DALAM PERSPEKTIF HADIS (Tinjauan Tentang Hadis Nafkah dalam Rumah Tangga) - Salmah Salmah (JURIS (Jurnal Ilmiah Syariah), 2018)
Moslem Tradition explained that livelihood was a husband obligation to feed his wife because of its relation between them. The obligation could be a living including other needs. The livelihood was depended on the husband’s capability to give it. If the husband had capability financially but did not fulfill that obligation, it means that he had tyrannized his family members. When fulfilling the livelihood had been assumed as a charity or a religious meal, a negligent husband might get a recompense in the day after.